Edukasi Kesehatan tentang Bahaya Konsumsi Junk Food pada Siswa di SMAN 1 Moyo Utara - Putri Adekayanti; Lina Eta Safitri (Jurnal Kabar Masyarakat, 2023)
Junk food consumption and its consequences have become a global public health problem. The pattern of excessive consumption of junk food is commonly found in adolescent groups. This can lead to nutritional problems such as underweight and obesity which can act as risk factors for various non-communicable diseases (PTM) such as hypertension, diabetes mellitus, cancer, cardiovascular disease and others. This community service activity aims to provide an understanding of the dangers of consuming junk food in adolescents through health education activities using power point media. This activity was carried out at SMAN 1 Moyo Utara with a total of 50 students in class X. The series of activities began with a pretest, delivery of counseling and posttest activities. The results of data analysis using the Wilcoxon test showed that there were differences in knowledge before and after counseling (0.021). With increased understanding, it is expected to be able to encourage students to be more selective in choosing the type of food to be consumed so that they can avoid various types of PTM.